Pengaruh Fasilitas Perpustakaan terhadap Minat Baca Siswa Tingkat Sekolah Dasar - Didit Darmawan; Abidha Khoiroh (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Reading is one method for improving personal abilities through understanding knowledge and information obtained from written texts. This study was conducted to assess the impact of library facilities on students' reading interest at the elementary school level. This study employed a qualitative approach. Data were collected using a literature study method derived from relevant scientific literature using qualitative data analysis methods related to "library facilities" and "reading interest" at the elementary school level. The analysis findings indicate that library facilities significantly influence students' reading interest. With a strategic location and attractive facilities, students can more easily use the library as a learning resource and as a place to develop reading habits. The results of this study reinforce the importance of optimizing school libraries in shaping students' literacy culture, particularly through the availability of services, collections, and access that support early reading habits. Therefore, good management of library services not only helps encourage students' interest in reading but also fosters a positive literacy culture throughout society.